Ferroptosis: The Silver Lining of Cancer Therapy - Tang, Zhengming; Huang, Zhijie; Huang, Yisheng; Chen, Yuanxin; Huang, Mingshu; Liu, Hongyu; Ye, Q. Adam; Zhao, Jianjiang; Jia, Bo (Frontiers in Cell and Developmental Biology, 2021)
Regulatory cell death has been a hot research topic in cancer therapy and one of the research directions to improve conventional clinical cancer treatment (e.g., chemotherapy, radiotherapy, etc.). Ferroptosis, a novel form of regulated cell death driven by iron-dependent lipid peroxidation, has increased since its discovery in 2012. Due to cancer cells' highly iron-dependent physiological properties, ferroptosis has also been gradually found to be promising in cancer therapy. Here we summarise the characteristics of ferroptotic cells, the associated mechanisms of occurrence and regulation, and the applications in cancer therapy: including how ferroptosis is induced in tumor cells and the use of ferroptosis in combination with other therapeutic modalities. Finally, we present the challenges of ferroptosis therapy in cancer and the future outlook to provide the basis and conditions for further research in the future